Pharmacology, toxicity and pharmacokinetics of acetylshikonin: a review - Zhiqin Zhang; Jie Bai; Yawen Zeng; Mengru Cai; Yu Yao; Huimin Wu; Longtai You; Xiaoxv Dong; Jian Ni (Taylor & Francis Group, 2020)
Context Acetylshikonin, a naphthoquinone derivative, is mainly extracted from some species of the family Boraginaceae, such as Lithospermum erythrorhizon Sieb. et Zucc., Arnebia euchroma (Royle) Johnst., and Arnebia guttata Bunge. As a bioactive compound, acetylshikonin has attracted much attention because of its broad pharmacological properties. Objective This review provides a comprehensive summary of the pharmacology, toxicity, and pharmacokinetics of acetylshikonin focussing on its mechanisms on the basis of currently available literature. Methods The information of acetylshikonin from 1977 to 2020 was collected using major databases including Elsevier, Scholar, PubMed, Springer, Web of Science, and CNKI. Acetylshikonin, pharmacology, toxicity, pharmacokinetics, and naphthoquinone derivative were used as key words. Results According to emerging evidence, acetylshikonin exerts a wide spectrum of pharmacological effects such as anticancer, anti-inflammatory, lipid-regulatory, antidiabetic, antibacterial, antifungal, antioxidative, neuroprotective, and antiviral properties. However, only a few studies have reported the adverse effects of acetylshikonin, with respect to reproductive toxicity and genotoxicity. Pharmacokinetic studies demonstrate that acetylshikonin is associated with a wide distribution and poor absorption. Conclusions Although experimental data supports the beneficial effects of this compound, acetylshikonin cannot be considered as a therapy drug without further investigations, especially, on the toxicity and pharmacokinetics.